The Future of Work: Pengaruh Digital Leadership terhadap Employee Wellbeing melalui Work Engagement pada Organisasi Hybrid - Edi Purwanto; Ahmad Sabri; Imam Tazali; Ery Suryanti; Teni Agustina (Trending: Jurnal Manajemen dan Ekonomi, 2026)
This study aims to analyze the effect of digital leadership on employee wellbeing through work engagement in hybrid organizations. This research employed an explanatory quantitative approach involving 100 employees who work in organizations implementing hybrid work systems, selected through purposive sampling. Data were analyzed using Structural Equation Modeling–Partial Least Squares (SEM-PLS) with SmartPLS by evaluating the measurement model and structural model. The findings show that digital leadership has a positive and significant effect on work engagement, work engagement has a positive and significant effect on employee wellbeing, and digital leadership also directly influences employee wellbeing. The indirect effect test confirms that work engagement partially mediates the relationship between digital leadership and employee wellbeing. These results indicate that effective digital leadership, characterized by clear communication, virtual coordination, emotional support, and adaptive digital culture, can strengthen employees’ engagement and wellbeing in hybrid work settings. The study suggests that organizations should develop human-centered digital leadership practices to maintain employee engagement, reduce digital work pressure, and promote sustainable wellbeing in the future of work.